ORGANIZATIONAL RESILIENCE THROUGH STRATEGIC TRANSFORMATION: ANALYSIS OF MANAGERIAL DECISIONS OF PT BLUE BIRD TBK IN FACING THE PANDEMIC CRISIS AND DIGITAL DISRUPTIONS - Anggun Ananda; Ani Rahmawati; Amanda Olivia; Three Daughters Daeli (CV Naskah Aceh, 2026)
This study aims to analyze the managerial decision-making process of PT Blue Bird Tbk in response to digital disruption and the COVID-19 pandemic crisis, as well as to examine its contribution to building organizational resilience. The research employs a qualitative approach with a descriptive case study design. Data were gathered through a documentary study of annual reports, audited financial statements, company publications, and relevant scientific literature covering the 2020–2025 period. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing/verification through pattern matching with theories of managerial decision-making, organizational resilience, and strategic transformation. The findings indicate that PT Blue Bird Tbk's success in navigating external pressures stems from adaptive, technology-driven managerial decisions. The company executed digital transformation by developing the MyBluebird application, expanding strategic collaborations with various digital platforms, and implementing service diversification through a multi-product, multi channel, and multi-payment approach. Furthermore, the company managed the pandemic crisis through operational efficiency and the expansion of logistics services. The results also demonstrate that PT Blue Bird Tbk successfully navigated the stages of organizational resilience namely anticipation, coping, and adaptation thereby sustaining business continuity and enhancing competitiveness amidst a shifting industrial landscape. Consequently, appropriate managerial decision-making, sustainable digital transformation, and adaptive leadership serve as the primary factors in establishing organizational resilience.